Два примера математического моделирования в области специальной электрометаллургии: процессы переплава и азотирования металлов - Жарди, А. (Автоматическая сварка, 2008)
A continuous research in the field of special electrometallurgy was carried out in France during the last 20 years, and numerical models of remelting processes (ESR or VAR) have been developed. In close collaboration with the E.O. Paton Electric Welding Institute a theoretical (i.e. modelling) and experimental study of the nitriding process of a Ni-20 % Cr alloy was performed.